Towards modeling of comprehensive assessment for licensing in higher education - Чередніченко, Ольга Юріївна; Янголенко, Ольга Василівна; Лютенко, Ірина Вікторівна; Пилипенко, Ганна Іванівна (Eastern-European Journal of Enterprise Technologies, 2013)
One of the main management problems in higher education establishment (HEE) is comprehensive assessment of its resources, which includes evaluation of their quality, performance and regulatory requirements satisfaction. The given work is devoted to the following problem: the evaluation of resources with regard to licensing requirements fulfillment. The goal of this research is to formalize and build mathematical models of resources assessment with respect to licensing requirements fulfillment. These models have to define the appropriate data processing methods of resources comprehensive assessment supporting licensing process in the university. In this work we consider the problem of comprehensive assessment of university’s resources for educational process (REP). The REP is a collection of separate resource elements (REs). A RE is defined as anything that is necessary to organize students’ learning, for example, it can be a classroom, a computer or a teacher. It is suggested to formalize this problem from three points of view: evaluating existing resources with respect to licensing requirements, finding maximal licensing volume provided by the existing resources and finding the required resources for the targeted licensing volume. The case study of these problems solving considers the evaluation of information and material resources. The formalization of these tasks in the form of appropriate mathematical models allows to make the next steps in the realization of information technology of licensing process support. These models and algorithms will form the basis for the development of information system of university resources assessment for licensing process support